Strategies to eliminate cervical cancer in China - Ji, Lu; Chen, Manli; Yao, Lan (Frontiers in Oncology, 2023)
Cervical cancer is a widely distributed disease, which is preventable and controllable through early intervention. World Health Organization has identified three key measures, coverage populations and coverage targets to eliminate cervical cancer. WHO and several countries have conducted model predictions to determine the optimal strategy and timing of elimination of cervical cancer. But specific implementation strategies need to be developed in the context of local conditions. China has a relatively high disease burden of cervical cancer, while having a low HPV vaccination rate and cervical cancer screening population coverage. The purpose of this paper is to review interventions and prediction studies for the elimination of cervical cancer, and to analyze the problems, challenges and strategies for the elimination of cervical cancer in China.